Language Production and Reception: A Processability Theory Study. Issue 4 (17th September 2013) - Spinner, Patti
Abstract : Pienemann's Processability Theory (PT) predicts an order of emergence of morphosyntactic elements in second language (L2) production data. This research investigates whether the same order of emergence can be detected in L2 reception data, specifically, data from a timed audio grammaticality judgment task (GJT). The results from three related studies are reported. Overall, evidence from two groups of learners of English as an L2 who took an audio GJT does not demonstrate the order of emergence predicted by PT. However, results from a production task followed the predicted order. These findings suggest that the processing routines in PT are operative during production only, raising questions about PT and the interconnectedness of the productive and receptive systems.